Anemia in Pregnant Women Attending the Antenatal Care Clinic, Mae Sot Hospital - Siriwong, Oranooch (Thai Journal of Obstetrics and Gynaecology, 2012)
Objectives: To determine prevalence and demographic characteristics of anemic Thai and Myanmar pregnant women attending the Antenatal Care Clinic, Mae Sot Hospital, Mae Sot, Tak province, Thailand. Materials and Methods: A cross-sectional study was conducted in 500 pregnant women between October 2011 and April 2012. Blood samples were obtained for determination of hematocrit level and screening for thalassemia. Information on age, ethnic affiliation, gestational age, gravida, level of education, occupation, household income, and area of residence were recorded. Results: Overall prevalence of anemia was 49% (Thai 36%; Myanmar 60%) and mean hematocrit level was 33.1±3.1%, anemia was significantly focus in second and third trimester more than first trimester of pregnancy (OR = 4.23, 95%CI 2.64 – 6.79 and OR = 6.30, 95%CI 3.35–11.85, respectively (p-value < 0.001). Conclusions: Anemia in both Thai and Myanmar pregnancy was common in Mae Sot.